Heard over the Iowa Birdline, June 1-November 15, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Summary of the Iowa Birdline update for June 1-November 15, 1992. Highlights of the update include sightings of a pair of birds with only two previous state records, a Lewis's Woodpecker and a female Vermilion Flycatcher were both seen in October. Other interesting observations were sightings of Black-throated Blue Warbler and a Yellow Rail in September at the IOU fall meeting. In addition, the Lake Red Rock area produced many exciting bird sightings, including a juvenile Laughing Gull, a Mississippi Kite, Red-throated Loons, and Pacific Loons. Epson - sheet feed